Phylogenetic relationships of chingia, sphaerostephanos and christella groups (Thelypteridaceae) from Sabah using rbcL gene sequences - Jacqueline Joseph (2010)
This study determined the phylogenetic relationship of Chingia, Sphaerostephanos and Christella groups and examined the grouping of the genera based on the resultant rbcl analyses in comparison to the morphological analyses, which were based on morphological descriptions provided by Holttum. The study sites consisted of Crocker Range Park and few of the West Coast Sabah area. In this phylogenetic study, rbcl gene marker was used to infer phylogenetic relationships of the study groups whereas morphological analyses was used to check the relationship based on the morphological characters gathered from Holttum. In the phylogenetic study of Chingia, Sphaerostephanos and Christella groups, 977 base pairs of DNA sequences were obtained from 32 samples representing the 3 groups of genera. The phylogenetic relationships and morphological analyses revealed that Sphaerostephanos is a taxonomically-problematic group especially for Pronephrium and Sphaerostephanos. The phylogenetic analyses found that there were two clades derived from the primitive Sphaerostephanos group, consisted of a monophyly advanced Sphaerostephanos clade and a monophyly clade of Chingia group and Christella group. Morphological analyses showed that Amphineuron and Christel/a were well-clustered into the Christella group. However, it was found that some of the Christel/a spp. ( C. subpubescens and C. papi/io) were established a lineage to Chingia group in the rbcl analyses. The grouping of Chingia and P/esioneuron into the Chingia group gained support from the morphological analyses but not completely supported by the rbd.. analyses since Chingia spp. ( C. c/avipi/osa and C. perrigida) were clustered into Christella group. Chingia and Christel/a were found to form a monophyletic clade together in both analyses. However, rbcl analyses does not support this grouping very well with <70% of bootstrap probability, and showed that Chingia group and Christella group were almost separated into two independent monophyly clade. The separation was in agreement with the morphological analyses that Christel/a clade and Chingia clade were split from each other to form their own monophyletic clade. It can be seen that Chingia group and Christella group were derived from a monophyletic group together and gradually evolved to form two independent groups. Pneumatopteris was verified being the genera under the Sphaerostephanos group since Pneumatopteriswas found appear in the monophyletic advanced Sphaerostephanos clade in the rbd.. analyses. Despite being that, the grouping of genera within Sphaerostephanos group cannot be displayed clearly. This could be due to the insufficiency of morphological characters used in morphological analyses were not strong enough to separate or distinguish certain genera into the Sphaerostephanos group. Genetic factors were also believed to influence the outcomes of rbcl analyses on the Sphaerostephanos group. Undoubtedly, more details studies should be carried out to support the proposed conclusions since this is the first time phylogenetic study conducted on Chingia, Sphaerostephanos and Christella groups of genera.